2003
DOI: 10.1023/b:phot.0000015465.86985.53
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Partitioning and Gas Exchange in Dalbergia sissoo seedlings under water stress

Abstract: Biomass, leaf water potential (Ψ l ), net photosynthetic rate (P N ), transpiration rate (E), stomatal conductance (g s ), leaf to air temperature difference (T diff ), and instantaneous water use efficiency (WUE) were measured in the seedlings of Dalbergia sissoo Roxb. grown under irrigation of 20 (W 1 ), 14 (W 2 ), 10 (W 3 ), and 8 (W 4 ) mm. Treatments were maintained by re-irrigation when water content of the soil reached 7.4 % in W 1 , 5.6 % in W 2 , 4.3 % in W 3 , and 3.2 % in W 4 . Seedlings in a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…Decrease in biomass in response to water stress is a commonly observed phenomenon (Guenni et al 2002, Singh andSingh 2003). For the two tested species, tree height, number of leaves, and leaf area were also decreased by water limitation.…”
mentioning
confidence: 72%
“…Decrease in biomass in response to water stress is a commonly observed phenomenon (Guenni et al 2002, Singh andSingh 2003). For the two tested species, tree height, number of leaves, and leaf area were also decreased by water limitation.…”
mentioning
confidence: 72%
“…The lower WUE under drought might be due to a greater effect on biomass production than on water-use. Under severe drought, a lower conductance of CO 2 and activity of photosynthetic enzymes in leaves of Dalbergia sissoo decreased photosynthesis and biomass, which reduced WUE (Singh and Singh 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusion also can be drawn from analyzing the responses of RWC. The efficiency indicator reflects the capacity of plants recovering to a favorable water status and their drought tolerance (Singh and Singh, 2003;Rosales-Serna et al, 2004). Although drought stress slightly decreased RWC as many previous studies have reported (Chartzoulakis et al, 2002;Rosales-Serna et al, 2004;Bai et al, 2006), Nl also increased RWC under a drought stress condition, and RWC increased with the increase of N supply under well-watered condition.…”
Section: Responses In Growth and Biomass Production To Drought Stressmentioning
confidence: 95%